STRENGTHENING TEACHERS' MENTAL HEALTH IN BUILDING SUPERIOR PERFORMANCE IN MADRASAH - Widiasari, Firdausa (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Teachers' mental health in building superior performance needs to be considered. This will affect teacher performance in the future. This research aims to strengthening teachers' mental well-being, which is considered essential for creating a superior work environment. The method used is qualitative by conducting a case study. With data analysis using data triangulation by looking for sources research information through reading scientific journals, reference books, news and related publication materials. The results of this research are, the importance of efforts to strengthen mental health, is a collaboration and must be integrated into the overall madrasa organizational culture. Providing good attention to teachers' mental health indirectly enables madrasas to create a positive and supportive educational environment for all parties involved. The aim of strengthening mental health in teachers is to motivate teachers psychologically to face busy work demands. The conclusion is that awareness of the importance of teacher mental health can also create a superior work environment, thereby having a positive impact on the quality of education in madrasas. By having a strong mentality, teachers can more easily synergize with fellow teachers, students and related parties in achieving the goals of madrasah education.